The Urgency of Strengthening the Right to Legal Aid for the Poor as a Manifestation of the Rule of Law in Indonesia's Criminal Justice System - Kasmudi Kasmudi; Prahasti Suyaman (International Forum of Researchers and Lecturers, 2026)
This article examines the urgency of strengthening the right to legal aid for the poor as a manifestation of the rule of law within Indonesia’s criminal justice system. Using a normative juridical approach, it analyzes Law Number 16 of 2011 on Legal Aid, its implementing regulations, constitutional provisions, criminal law reform, and international fair trial standards. The study finds that Indonesia has established a significant legal framework to provide free legal services, promote access to justice, and uphold equality before the law. Nevertheless, several challenges remain, including limited eligibility criteria, administrative barriers in proving poverty, inadequate access to legal assistance during the early stages of investigation, weak institutional referral mechanisms, insufficient funding, unequal distribution of accredited legal aid providers, and limited quality assurance. To address these issues, legal aid should be strengthened through emergency assistance mechanisms, mandatory referrals by law enforcement officers, increased and sustainable funding, more equitable distribution of legal aid organizations, and stronger supervision of service quality. These reforms are essential to ensure that formal legal equality is translated into substantive justice for poor suspects and defendants.